Behavioral Portrayal of Gadgets in School-age Children in Integrated Islamic Elementary School - Nanda, Gilang Ayu Dwi; Sari, Irma Mustika (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: Today technology is very rapidly growing. Gadgets as devices often used in modern times can make human activities easier. Where today, the proliferation of schoolchildren using gadgets where children allow persistent use of gadgets regardless of the possible health effects. Purpose: elaborated on the behavior of gadgets use in school-age children in ntegrated Islamic Elementary School (SDIT) Az Zahra 1 Sragen. Method: quantitative descriptive, 59 respondents by simple random sampling technique. The instruments used are questionnaires and data analytics using univariate analysis. Results: as many as 39 respondents (66.1%) use gadgets >2 hours/day, lying position 35 respondents (59.3%), on a dim screen 44 respondents (76.6%) and in the light room by 45 cm (76.3%), at a distance of <30 cm (52.5%) and the behavior of gadgets use in children are less <50% (64.4%). Conclusion: the behavior of the use of gadgets in children is more than 2 hours a day, by using lying position, by the use of gadgets on the dim screen and the bright room, and the use of gadgets at a distance of less than 30 cm.